Diagnostic Performance of CT/MRI Liver Imaging Reporting and Data System v2017 for Hepatocellular Carcinoma: A Systematic Review and Meta‐Analysis. (19th March 2020) - Lee, Sunyoung; Kim, Seung‐Seob; Roh, Yun Ho; Choi, Jin‐Young; Park, Mi‐Suk; Kim, Myeong‐Jin
Abstract: Background & Aims: The liver Imaging Reporting and Data System (LI‐RADS) is a comprehensive system for standardizing liver imaging in patients at high risk for hepatocellular carcinoma (HCC). We performed a meta‐analysis to determine the diagnostic performance of the LR‐5 category for HCC and the pooled proportions of HCCs in each LI‐RADS category using CT/MRI LI‐RADS v2017. Methods: We searched multiple databases for original studies reporting on the diagnostic accuracy of CT/MRI LI‐RADS v2017. Random‐effects models were used to determine the summary estimates of the diagnostic performance of the LR‐5 category and the pooled proportions of HCCs for each LI‐RADS category. Risk of bias and concerns regarding applicability were evaluated with the Quality Assessment of Diagnostic Accuracy Studies‐2 tool. Results: Fourteen studies (3 prospective studies and 11 retrospective studies) were included in the final analysis, consisting of 2056 patients, 2589 observations, and 1693 HCCs. The pooled per‐observation sensitivity was 67% (95% confidence interval [CI], 62%‐72%) with specificity of 92% (95% CI, 88%‐95%) in the LR‐5 category of CT/MRI LI‐RADS v2017 for diagnosing HCC. The pooled proportions of HCCs were 0% (95% CI, 0%‐0%) for LR‐1, 4% (95% CI, 0%‐8%) for LR‐2, 34% (95% CI, 23%‐44%) for LR‐3, 67% (95% CI, 53%‐81%) for LR‐4, and 92% (95% CI, 87%‐96%) for LR‐5. The proportions of HCCs were significantly different among LI‐RADS categories 1‐5 ( P  = .034). Conclusions: The LR‐5 category of CT/MRI LI‐RADS v2017 shows moderate sensitivity and high specificity for diagnosing HCC. Higher LI‐RADS categories contained higher proportions of HCCs.